2021
DOI: 10.1002/ppp3.10188
|View full text |Cite
|
Sign up to set email alerts
|

Urban park visitor preferences for vegetation – An on‐site qualitative research study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 66 publications
0
13
0
2
Order By: Relevance
“…The characteristics of more wild nature, therefore, may give individuals the opportunity to have more profound, varied and more frequent interactions with nature. Other studies have found that the type of nature matters for individual connectedness to nature and frequency of visitation (Colléony et al, 2017), as well as finding that individuals express preferences for more of specific natural elements in urban green spaces such as trees (Talal et al, 2021). While urban nature areas in general are important to address the extinction of experience (Shanahan et al, 2015), specific types of nature sites can increase opportunity for meaningful interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of more wild nature, therefore, may give individuals the opportunity to have more profound, varied and more frequent interactions with nature. Other studies have found that the type of nature matters for individual connectedness to nature and frequency of visitation (Colléony et al, 2017), as well as finding that individuals express preferences for more of specific natural elements in urban green spaces such as trees (Talal et al, 2021). While urban nature areas in general are important to address the extinction of experience (Shanahan et al, 2015), specific types of nature sites can increase opportunity for meaningful interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Complementariamente, en el contexto estudiado, gran parte de los participantes provienen de entornos rurales o tienen acceso frecuente a estos, lo que incrementa su conocimiento y actitudes positivas hacia las plantas (Whitburn et al, 2020). Esto también refleja la importancia que los niños dan a la experiencia directa en la naturaleza, puesto que su interacción con la vegetación puede proporcionar beneficios en la salud, y brindar oportunidades de relajación y recreación (Talal et al, 2021).…”
Section: Discussionunclassified
“…Pertimbangan dalam pemilihan pohon ini adalah daya serap polutan yang tinggi, sehingga mampu dalam menunjang fungsi ekologis taman kota. Penilaian kesesuaian tanaman di taman kota ditentukan oleh jenis tanaman yang ditanam sesuai dengan kriteria dalam Peraturan menteri Perencanaan Umum Nomor 5 Tahun 2008, jenis dan fungsi taman serta penataan taman (Menteri Perencanaan Umum, 2008;Talal et al, 2021;Mahmoud and Omar, 2015). Penanaman serta penataan vegetasi pada taman kota perly mempertimbangkan beberapa aspek seperti sifat fisik dari vegetasi, kegunaan, jarak tanam, serta nilai estetika yang akan muncul.…”
Section: Delonix Regia Danunclassified